The Effect Of Financial Literacy And Lifestyle On Employee Financial Management At Regional Secretariat, Lebong District - Rusman Adinata; Karona Cahya Susena; Wagini Wagini (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the effect of financial literacy and lifestyle on employee financial management at the Regional Secretariat of Lebong Regency. The sample in this study was 79 employees at the Regional Secretariat of Lebong Regency who had become civil servants. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing.The multiple regression results show a positive direction of regression with the equation Y = 8.445 + 0.239X1 + 0.227 X2. Financial literacy has a significant influence on employee financial management at the Regional Secretariat of Lebong Regency because a significant value of 0.013 is smaller than 0.05. This illustrates that as financial literacy increases, employee financial management will also increase. Lifestyle has a significant influence on employee financial management at the Regional Secretariat of Lebong Regency because a significant value of 0.000 is less than 0.05. This illustrates that as lifestyle increases, employee financial management will also increase. Financial literacy and lifestyle have a significant simultaneous influence on employee financial management at the Regional Secretariat of Lebong Regency because a significant value of 0.000 is less than 0.05.